Elderly trauma: the two years experience of a University-affiliated Emergency Department - Yildiz, M.; Bozdemir, M. N.; Kilicaslan, I.; Atescelik, M.; Gurbuz, S.; Mutlu, B.; Gurger, M. (Verduci Publisher, 2012)
Objective: The elderly population is steadily increasing in the modern world. The aging of the population has led to an increase in geriatric trauma. Elderly trauma patients present unique challenges and face more significant obstacles in recovery compared to younger patients. This study is designed to determine the epidemiologic data of trauma in elderly patients and to contribute to the national trauma database. Materials and Methods: We prospectively collected the data of trauma patients, aged 65 and older, presenting to our Emergency Department. Patients' data, including demographic data, diagnosis, prognosis, trauma scores [Glasgow Coma Scale (GCS), Injury Severity Score (ISS)], mortality, body regions of injury and outcomes were analyzed. Results: During the study period, 407 patients, of whom 63.9% were males and 36.1% females, were admitted to our Emergency Department. The mean age of the patients was 73.14 +/- 7.14 years. Falls (59%) accounted for the most common cause of injury. The mean GCS and mean ISS were 14.39 and 10.69, respectively. Trauma to extremities was the most frequent body region of injury (56.3%). A total of 149 patients were hospitalized. The mean hospital length of stay was 11.07 +/- 14 days. The mortality rate was found to be 6.4%. Head trauma was the most common cause in mortality. Conclusions: The risk of trauma in the elderly population is higher. As a result of the decrease in physiological reserve and lack of adaptation to trauma, elderly trauma patients require more aggressive management and a multidisciplinary approach. Further studies are needed for data of elderly trauma patients.
Keywords: Aged; Wounds and injuries; Emergency service; Hospital; Epidemiology